2016
DOI: 10.7759/cureus.655
|View full text |Cite
|
Sign up to set email alerts
|

Novel Transabdominal Motor Action Potential (TaMAP) Neuromonitoring System for Spinal Surgery

Abstract: IntroductionMinimally invasive lateral lumbar interbody fusion (LLIF) approaches to the lumbar spine reduce patient morbidity compared to anterior or posterior alternatives. This approach, however, decreases direct anatomical visualization, creating the need for highly sensitive and specific neurophysiological monitoring. We seek to determine feasibility in 'transabdominal motor action potential (TaMAP)' monitoring as an assessment for the integrity of the neural elements during lateral-approach surgeries to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Additional studies are needed to further corroborate these findings and continue to examine the benefits of this technique. There is currently only one other study to our knowledge discussing TaMAP, as it is a relatively novel tool [17]. Given that the current study involved only a case of a malpositioned screw, future research should involve an experimental follow-up with a larger, more comprehensive set of data points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional studies are needed to further corroborate these findings and continue to examine the benefits of this technique. There is currently only one other study to our knowledge discussing TaMAP, as it is a relatively novel tool [17]. Given that the current study involved only a case of a malpositioned screw, future research should involve an experimental follow-up with a larger, more comprehensive set of data points.…”
Section: Discussionmentioning
confidence: 99%
“…TaMAP recordings can be obtained as a function of stimulus current, offering real-time functional feedback. Studies on porcine models have shown TaMAP to be a beneficial neuromonitoring alternative to the complications and limitations caused by a previously used technique transcranial motor evoked potential (TcMEP) [17][18]. Thus, the current study seeks to validate the use of TaMAP as a safer, more effective alternative to prior methods and is the first to examine this technique in human participants.…”
Section: Tamap As a Neuromonitoring Techniquementioning
confidence: 99%
See 1 more Smart Citation